Sodium menu labelling: priorities for research and policy. Issue 6 (9th April 2021) - Alexander, Eleanore; Rutkow, Lainie; Gudzune, Kimberly A; Cohen, Joanna E; McGinty, Emma E
Abstract: Objective: To understand the different Na menu labelling approaches that have been considered by state and local policymakers in the USA and to summarise the evidence on the relationship between Na menu labelling and Na content of menu items offered by restaurants or purchased by consumers. Design: Proposed and enacted Na menu labelling laws at the state and local levels were reviewed using legal databases and an online search, and a narrative review of peer-reviewed literature was conducted on the relationship between Na menu labelling and Na content of menu items offered by restaurants or purchased by consumers. Setting: Local and state jurisdictions in the USA Participants: Not applicable. Results: Between 2000 and 2020, thirty-eight laws – eleven at the local level and twenty-seven at the state level – were proposed to require Na labelling of restaurant menu items. By 2020, eight laws were enacted requiring chain restaurants to label the Na content of menu items. Five studies were identified that evaluated the impact of Na menu labelling on Na content of menu items offered by restaurants or purchased by consumers in the USA. The studies had mixed results: two studies showed a statistically significant association between Na menu labelling and reduced Na content of menu items; three showed no effects. Conclusion: Data suggest that Na menu labelling may reduce Na in restaurant menu items, but further rigorous research evaluating Na menu labelling effects on Na content of menu items, as well as on the Na content in menu items purchased by consumers, is needed.